Enantioselective aerobic oxidative cross-dehydrogenative coupling of glycine derivatives with ketones and aldehydes via cooperative photoredox catalysis and organocatalysis. Issue 18 (27th April 2020) - Yang, Xiaorong; Xie, Zhixiang; Li, Ying; Zhang, Yuan
Abstract : A visible-light-induced enantioselective aerobic oxidative cross-dehydrogenative coupling between glycine derivatives and simple ketones or aldehydes is achieved. Abstract : The combination of photoredox catalysis and enamine catalysis has enabled the development of an enantioselective aerobic oxidative cross-dehydrogenative coupling between glycine derivatives and simple ketones or aldehydes, which provides an efficient approach for the rapid synthesis of enantiopure unnatural α-alkyl α-amino acid derivatives in good yield with excellent diastereo- (up to >99 : 1) and enantioselectivities (up to 97% ee). This process includes the direct photoinduced oxidation of glycine derivatives to an imine intermediate, followed by the asymmetric Mannich-type reaction with an enamine intermediate generated in situ from a ketone or aldehyde and a chiral secondary amine organocatalyst. This mild method allows the direct formation of a C–C bond with simultaneous installation of two new stereocenters without wasteful removal of functional groups.